A study of coupling reaction to synthesize diphenylmethane derivatives - Bhatti, Huma Aslam; Zaheer, Qurat-Ul-Ain; Khatoon, Memoona; Light, Mark Edward; Hameed, Abdul (European Journal of Chemistry, 2014)
The class of compounds having diphenylmethane framework occupy a distinct place in natural bioactive compounds and also serve as useful intermediates in various commercially important synthetic molecules. Conventionally, Friedel-Craft type reactions were used to synthesize such diphenylmethane derivatives. However, herein we report a unique approach in which, two benzyl alcohol molecules were coupled in the presence of different halogenating agents (SOCl2, PBr3 and MeSO2Cl) to afford the desired diphenylmethane derivative, bis(2,4-bis(benzyloxy)-5-methoxyphenyl)methane. It has been found that the coupling reaction is strongly influenced by the electronic effects and number of the substituents on the phenyl ring. The resultant compound, bis(2,4-bis(benzyloxy)-5-methoxyphenyl)methane, was obtained in excellent yield (83-85%) and completely characterize with different spectroscopic techniques.